1989
DOI: 10.1002/j.1552-4604.1989.tb03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of H2‐receptor Antagonists

Abstract: The type II histamine receptor antagonists, cimetidine and ranitidine, widely used in treatment of peptic ulcer disease have been reported to cause bradycardia. To evaluate the cardiovascular effects of H2 antagonists nineteen healthy volunteers were entered into a double-blind crossover comparison of cimetidine 300 mg qid, ranitidine 150 mg bid, and placebo. Subjects ingested study medicine for 7 days prior to being tested by the Bruce Exercise Test. Heart rate, blood pressure, oxygen consumption, expiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Hinrichsen et al [5] in a double-blind study, showed no significant effect of oral ranitidine on heart rate, blood pressure or systolic time intervals, Similar results were obtained from another, double-blind study, that evaluated the effects of oral ranitidine and cimetidine on heart rate, blood pressure, Oz consumption, expiratory volume, fractional expiratory Oa and CO2 [6]. Yet, the sinus node of a neonate may be specifically sensitive to negative chronotropic acting agents.…”
Section: Discussionsupporting
confidence: 63%
“…Hinrichsen et al [5] in a double-blind study, showed no significant effect of oral ranitidine on heart rate, blood pressure or systolic time intervals, Similar results were obtained from another, double-blind study, that evaluated the effects of oral ranitidine and cimetidine on heart rate, blood pressure, Oz consumption, expiratory volume, fractional expiratory Oa and CO2 [6]. Yet, the sinus node of a neonate may be specifically sensitive to negative chronotropic acting agents.…”
Section: Discussionsupporting
confidence: 63%
“…Results of previous studies using H 2 antagonists reported no effects on blood pressure or heart rate during exercise (Saltissi et al 1981;Hughes et al 1989;McCord et al 2006). However, it is worth considering that possible cardiovascular effects of histamine might have been mitigated by the nature of the exercise protocols used in these studies.…”
Section: Introductionmentioning
confidence: 93%
“…While Saltissi et al (1981) and Hughes et al (1989) conducted chronic H 2 receptor blockade, effects of acute blockade on the cardiovascular response to short bouts of submaximal dynamic exercise have not been examined.…”
Section: Introductionmentioning
confidence: 98%
“…Although limited findings about adverse effects of these three categories (D 2 and H 2 antagonists and proton pump inhibitors), on both mothers and neonates are reported, their negative cardiovascular effects were the subject of many articles during the last few years [15][16][17][18][19][20][21][22][23]. From the most pronounced clinically reported effects mentioned in the literature are: ventricular arrhythmia, significant fall in stroke volume and cardiac output, blockage of pre-synaptic auto receptors, remarkable delay in cardiac repolarization associated with QT interval prolongation.…”
Section: Drugmentioning
confidence: 99%